Cordia verbenacea DC. (Boraginaceae): quality control parameters, phytochemical screening and evaluation of anti-Candida activity - Scardelato, J. A. [UNESP]; Santos, A. G. [UNESP]; Pietro, R. C.L.R. [UNESP]; Sacramento, L. V.S. [UNESP] (My University, 2016)
Cordia verbenacea occurs all along the Brazilian coast and it is widely used to treat various inflammatory processes. In the present study we aimed to describe a physical-chemical profile and pharmacognostic vegetal drug as well as to draw a chromatographic profile of the crude extract and its fractions. We have observed the occurrence of secondary metabolites such as flavonoids, terpenes and tannins. The study of anti-Candida activity of extracts indicated the best results for C. glabrata (9.77-36.06 μg.mL-1), intermediate values for C. krusei (312.5-625 μg.mL-1), C. tropicalis (312.5-625μg.mL-1) and high values for C. albicans (1250>2500 μg.mL-1) and C. parapsilosis 625-2500 μg.mL-1).
Cordia verbenacea: parâmetros físico-químicos, fitoquímico da droga vegetal e atividade anti-Candida do extrato hidroetanólico e suas frações
Keywords: anti-Candida; Cordia; phytochemical